One new subspecies of the genus Ultragryllacris Gorochov & Dawwrueng, 2015 (Orthoptera: Gryllacrididae: Gryllacridinae) and its new record from China - Bin, Wei; Bian, Xun (Zootaxa, 2021)
The orthopteran genus Ultragryllacris Gorochov & Dawwrueng, 2015 is documented as a new record from China, and one new subspecies viz. U. pulchra rubricapitis ssp. nov. is described from Yunnan Province, China. All the examined specimens are deposited in Guangxi Normal University.